Expression of GNSS Positioning Error in Terms of Distance - Filić, Mia; Filjar, Renato; Ševrović, Marko (Promet - Traffic&Transportation, 2018)
This manuscript analyzes two methods for Global Navigation Satellite System positioning error determination for positioning performance assessment by calculation of the distance between the observed and the true positions: one using the Cartesian 3D rectangular coordinate system, and the other using the spherical coordinate system, the Cartesian reference frame distance method, and haversine formula for distance calculation. The study shows unresolved issues in the utilization of position estimates in geographical reference frame for GNSS positioning performance assessment. Those lead to a recommendation for GNSS positioning performance assessment based on original WGS84-based GNSS position estimates taken from recently introduced data access from GNSS software-defined radio (SDR) receivers.